2010
DOI: 10.3390/ijms11093266
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Peroxidase and Polyphenol Oxidase: Substrate Specificity and Active Site Comparison

Abstract: Peroxidases (POD) and polyphenol oxidase (PPO) are enzymes that are well known to be involved in the enzymatic browning reaction of fruits and vegetables with different catalytic mechanisms. Both enzymes have some common substrates, but each also has its specific substrates. In our computational study, the amino acid sequence of grape peroxidase (ABX) was used for the construction of models employing homology modeling method based on the X-ray structure of cytosolic ascorbate peroxidase from pea (PDB ID:1APX),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…Peroxidases (POD) are oxidoreductases that are highly resistant to high temperatures. They catalyse the oxidation of various substrates, including phenolic compounds, in the presence of hydrogen peroxide to final dark-pigment products (Nokthai et al, 2010). Most importantly, these enzymes are induced by stress conditions, for example wounding that usually take places in the food production chain.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxidases (POD) are oxidoreductases that are highly resistant to high temperatures. They catalyse the oxidation of various substrates, including phenolic compounds, in the presence of hydrogen peroxide to final dark-pigment products (Nokthai et al, 2010). Most importantly, these enzymes are induced by stress conditions, for example wounding that usually take places in the food production chain.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, as there is high amount of a particular phenolics, it is natural that the amount of PPO enzymes present will react accordingly resulting in a correlation. However, despite having low amount of both rutin and chlorogenic acid, P. americana still fitted in the correlation curve, as its PPO activity was already very low, hence, its capability to degrade/react with polyphenols are also limited, and therefore in this case, the amount of enzyme is a limiting factor for enzymatic reaction (Nokthai, Lee, & Shank, ).…”
Section: Resultsmentioning
confidence: 99%
“…1, was the best. Nokthai et al (2010) analyzed the active site of PPO by molecular modeling. They found that epicatechin and catechin had high affinity with the enzyme.…”
Section: Resultsmentioning
confidence: 99%